Climatic Correlation with Vegetation and Soils for Uttar Pradesh - Singh, S. N. (Indian Forester, 1973)
The paper aims to make an assessment of the extent, , climate controls the distribution or vegetation and soils any region of the globe. For this purpose the region of Uttar Pradesh, an Important and extensive province of this country has been chosen, preferably because it shows almost all types of climate. The climates of the province have been delineated -according to rational scheme of Thornthwaite (1948) in its thermal regime and the scheme of Thorathwaite and Mather (1955) in its moisture regime. The climatic correlation with the vegetation types of the province has been made, It is concluded that moisture factor is the chief factor controlling the distribution of vegetation ,type. However in the Northern hilly region thermal factor outweighs the moisture factar. The distribution of soils has been compared with that of climates. Though the role of climate in development and reshapement of soils is not that significant al in the case of vegetations, still climates stands thee most important factor. It Is also concluded that none of the three great patterns of earth’ viz. climate, vegetation and soils can be subjected to comprehensive and detailed study in isolation of the other two. Thus complete picture of the environment can be seen only when all the three are studied together.